Diabetes type 2 risk gene Dusp8 is associated with altered sucrose reward behavior in mice and humans. Issue 1 (1st November 2020) - Baumann, Peter; Schriever, Sonja C.; Kullmann, Stephanie; Zimprich, Annemarie; Peter, Andreas; Gailus‐Durner, Valerie; Fuchs, Helmut; Hrabe de Angelis, Martin; Wurst, Wolfgang; Tschöp, Matthias H.; Heni, Martin; Hölter, Sabine M.; et al.
Abstract: Background: Dusp8 is the first GWAS‐identified gene that is predominantly expressed in the brain and has previously been linked with the development of diabetes type 2 in humans. In this study, we unravel how Dusp8 is involved in the regulation of sucrose reward behavior. Methods: Female, chow‐fed global Dusp8 WT and KO mice were tested in an observer‐independent IntelliCage setup for self‐administrative sucrose consumption and preference followed by a progressive ratio task with restricted sucrose access to monitor seeking and motivation behavior. Sixty‐three human carriers of the major C and minor T allele of DUSP8 SNP rs2334499 were tested for their perception of food cues by collecting a rating score for sweet versus savory high caloric food. Results: Dusp8 KO mice showed a comparable preference for sucrose, but consumed more sucrose compared to WT mice. In a progressive ratio task, Dusp8 KO females switched to a "trial and error" strategy to find sucrose while control Dusp8 WT mice kept their previously established seeking pattern. Nonetheless, the overall motivation to consume sucrose, and the levels of dopaminergic neurons in the brain areas NAcc and VTA were comparable between genotypes. Diabetes‐risk allele carriers of DUSP8 SNP rs2334499 preferred sweet high caloric food compared to the major allele carriers, rating scores for savory food remained comparable between groups. Conclusion: Our data suggest a novel role for Dusp8 in the perception of sweet high caloric food as well as in the control of sucrose consumption and foraging in mice and humans. Abstract : Sucrose reward studies in female mice deficient for the MAPK phosphatase dual specificity phosphatase 8 (Dusp8) revealed increased sucrose consumption, unaltered sucrose preference, and perturbed sucrose‐seeking behavior. Human carriers of DUSP8 diabetes‐risk SNP rs2334499 preferred sweet high caloric food compared to the major allele carriers. These data suggest a new role for Dusp8 in the perception of sweet high caloric food as well as in sucrose consumption and foraging.